Formulation and Characterization of Nanoemulsion Turmeric oil - Hendrika, Yan; Aulia, Zulikho; Mardhiyani, Dini (Poltekkes Kemenkes Riau, 2023)
Turmeric oil is an essential oil derived from turmeric (Curcuma domestica). Turmeric oil is known to have antiinflammatory, antibacterial, antifungal and antioxidant activities. Nanoemulsions have the advantage of improving drug absorption and bioavailability. The purpose of the formulation of this nanoemulsion is to know the characteristics of turmeric oil nanomulsions. The formula consists of F1 (5%), F2 (10%), and F3 (15%). The preparation assessment covers organoleptic, pH, viscosity, stability, particle size, and zeta potential. The nanoemulsion preparation is produced in a thick yellow, typical odor of turmeric oil, with a pH of 6.8-7, a viskosity of 23-29 Cps, transmission values of 43.3-74.6%, droplet sizes at F1, F2, F3 of 23.2 nm, 203.8 nm, and 298.7 nm and zeta values potentials F1, F2 - 18.5mV, F 2 - 13.4mv, and F3 -8,5mV, all of the formulas well physically stable by the cracking, sedimentation and tubidity.